A New Vestibular Stimulation Mode for Motion Sickness With Emphatic Analysis of Pica - Zhi-Hao Zhang (Frontiers in Behavioral Neuroscience, 2022)
Motion sickness (MS) was frequently introduced for rodents in research work through passive motion that disturbed vestibular signals in the presence of visual and aleatory, proprioceptive inputs. Inducement of MS in this way causes conflicting signals that activate intermixed neural circuits representing multimodal stimulation. From reductionism, a lab setup to elicit rat MS via vestibular stimulation was configured in the present study for MS study in connection with dissection of the central vestibular component causally underlying MS. The individual animal was blinded to light with a custom-made restrainer, and positioned at an inclination of 30° for otolith organs to receive unusual actions by gravitoinertial vector. Following a 2-h double-axis (earth–vertical) rotation involving angular acceleration/deceleration, a suit of behaviors characterizing the MS was observed to be significantly changed including pica (eating non-nutritive substance like kaolin), conditioned taste avoidance and locomotion (p < 0.05). Notably, for the statistical hypothesis testing, the utility of net increased amount of kaolin consumption as independent variables in data processing was expounded. In addition, Fos-immunostained neurons in vestibular nucleus complex were significantly increased in number, suggesting the rotation-induced MS was closely related to the vestibular activation. In conclusion, our work indicated that the present setup could effectively elicit the MS by disturbing vestibular signals in rat in the context of well-controlled proprioceptive inputs and lack of visual afference.